Settlement of Geosynthetic Encased Stone Columns Liquefaction Condition in Box Culvert - Maftuh Ahnan; Putera Agung Maha Agung (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
When the box culvert system is placed on a sandy soil layer with a relatively low bearing capacity and is disposed to potential liquefaction, the soil layer must be repaired to avoid damages to the box culvert structure. The proposed method is Geosynthetic Encased Stone Columns (GESC) to increase the bearing capacity and anticipated the liquefaction potential. however, to meet the criteria for a stable and safe GESC soil improvement in liquefaction conditions, the value of the settlement must meet the requirements for the settlement permit limit. This research was conducted to determine the potential for liquefaction at the study location, to calculate the value of single and group settlements in liquefaction conditions and to analyze the stability of single and group settlements including safe or unsafe in liquefaction conditions. Analysis of liquefaction potential was analyzed based on SPT data using the Valera and Donovan method, and settlement analysis applied the Almeida and Alexiew method. The analysis shows that potential liquefaction due to an earthquake with a magnitude of 9.0 SR will be at a depth of 4 to 8 m. Single and group settlements (144 sets) with an installation distance of 1.2 m with a diameter of 0.4 m and at a depth of 10 m are 246.23 and 214.92 mm, respectively. The entire GESC system is considered to be in an unstable and unsafe condition against potential liquefaction and box culvert loading.